Assessing Reproductive Decision-making Among HIV-Positive Women in Kumasi, Ghana - Alicia E. Hersey, BA; Betty Norman, MBChB, DTM&H; Rebecca Reece, MD (Global Health and Education Projects, Inc., 2019)
Background or Objectives: HIV-positive women have higher rates of unmet need for contraception and unintended pregnancy and face unique obstacles in accessing family planning services, such as healthcare- related stigma and disclosing HIV status to partners. This study characterizes factors that influence the reproductive decision-making of women living with HIV and identifies areas for improvement in reproductive counseling in Kumasi. Methods: In this cross-sectional study, HIV-positive women, ages 18 to 45 years, presenting for care at Komfo Anokye Teaching Hospital between June and August 2017 were interviewed using structured surveys. Information gathered included demographics, method of contraceptive use, initiation of anti- retroviral therapy (ART), knowledge and use of contraception, and future reproductive plans. The primary outcome was current family planning use and future reproductive desire. Univariate analysis was used to characterize the demographics of the study group. Bivariate analysis including Chi-squared test was employed to assess the association between use of family planning between women with an HIV-positive and HIV-negative partner, with significance set at p < 0.05. Results: A total of 88 women were interviewed. The unmet need for contraception was 10%. Among all sexually active women, 26% did not use contraception. Fewer women with HIV-negative or untested partners were using contraception (65% and 67%, respectively), compared to women with HIV-positive partners (93%). Partner preference was the most common reason cited for not using a method of contraceptive (46%). Similar trends were found in future reproductive desires based on age cohorts, partner status, and use of family planning. Conclusion and Global Health Implications: Significant barriers to family planning use among HIV- positive women remain, especially those with a serodiscordant partner. Most partners were aware of their partner's HIV status. This highlights an important opportunity to include partners in HIV and contraceptive counseling. Key words: • HIV • Family planning • Contraception • LARC • Serodiscordant • Ghana • Africa   Copyright © 2019 Hersey et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.